Hubungan Pola Makan dengan Kadar Gula Darah Penderita Diabetes Melitus Tipe 2 : Literature Review - Kuwanti, Elly; Budiharto, Ichsan; Fradianto, Ikbal (Universitas Malahayati, 2023)
ABSTRACT There is a change in eating patterns at this time. Selection of food menus and unhealthy lifestyles are increasingly widespread in all levels of society that affect diseases, one of which is diabetes mellitus. A lot of literacy that studies about diet and how it affects the incidence of diabetes mellitus is still too much confusion. To determine the relationship between diet and blood sugar levels in type 2 diabetes mellitus patients. Using a literature review design with SPIDER analysis technique. The keywords in English are